Pulmonary expression of ICAM-1 and LFA-1 in experimental Goodpasture's syndrome. - Hill, P. A. (1994)
The functional importance of ICAM-1 and its ligands, the beta 2-integrins, in leukocytic accumulation in pulmonary injury has been recently demonstrated in experimental models of lung disease. However, the exact location of these adhesion molecules remains unknown. In the current study we have used immunogold ultrastructural techniques to define the precise location of ICAM-1 in the lung and its interaction with beta 2-integrin expressing leukocytes in the early stages of experimental Goodpasture's (GP) syndrome in the rat. In normal animals there is strong constitutive ICAM-1 expression on the luminal surface of the alveolar epithelium that is confined to type I cells and completely absent from type II cells. Constitutive expression of ICAM-1 on the pulmonary capillary endothelium is comparatively weak. In GP syndrome there is an increase in ICAM-1 expression, which is still confined to the alveolar type I epithelial cells and capillary endothelium. This is associated with an early (1.5 hours) influx of CD18 expressing polymorphonuclear leukocytes, which are seen migrating into alveoli and the pulmonary interstitium. There is a later (6-12 hours) influx of CD11a/CD18 expressing macrophages which are present in the interstitium and in large numbers in the alveolar spaces, where they are very closely apposed to and adherent to the alveolar epithelium. This is the first study to demonstrate the precise ultrastructural location of ICAM-1 in the normal rat lung and in disease. In vivo administered antibody to ICAM-1 gains access to the extravascular sites within the lung, in particular the surface of alveolar type I epithelial cells, and this raises the possibility that beneficial effects of such antibodies may extend beyond their ability to inhibit interactions between leukocytes and endothelial cells.